A constitutive model for granular materials subjected to a large stress range. (April 2020) - Liu, Lin; Yao, Yangping; Luo, Ting; Zhou, Annan
Abstract: A simple constitutive model is presented to represent the behavior of granular materials subjected to a large stress range by introducing a revised normal compression line with a limit void ratio ( e L ) in the double logarithmic scale and a state parameter ( ξ ) to quantify the state of granular materials. In the proposed model, a drop-shaped yield surface is employed and a unified hardening parameter ( H ) that is a function of the state parameter ( ξ ) is developed to govern the hardening process. The model is first established in the triaxial compression stress state and then is extended to the general stress state through the transformed stress (TS) method. Adopting a single set of material parameters, the proposed model is verified against the experimental results of various tests on Cambria sand at different confining pressures (0.25–68.9 MPa), including the data of isotropic compression test and drained/undrained triaxial compression/extension tests.